2022
DOI: 10.3389/fmed.2022.896538
|View full text |Cite
|
Sign up to set email alerts
|

Does Infertility Stress Impair Sexual Function in Infertile Women and Men? A Cross-Sectional Study in Iran

Abstract: BackgroundThe issue of infertility is a worldwide challenge, estimated to affect around 50 million couples. This study aimed to evaluate the relationship between infertility stress and sexual function in men and women with infertility.MethodsIn this cross-sectional study, 300 men and women with infertility were recruited. A demographic questionnaire, the Fertility Problem Inventory, the Female Sexual Function Scale (FSFI), and the International Index of Erectile Function (IIEF) were used to collect data. Indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…One Indian study said that 39.3%, 12.6%, and 13.6% of infertile women in Central India are 25-29, 20-24, and 30-34 years, respectively [96]. In Nepal, the average age of infertile women was 27.44±5.214 years attending the infertility clinic of a tertiary hospital [142]. Another Nepalese study reported that the majority (51.52%) of infertility females were aged 26-30 [143].…”
Section: Discussionmentioning
confidence: 99%
“…One Indian study said that 39.3%, 12.6%, and 13.6% of infertile women in Central India are 25-29, 20-24, and 30-34 years, respectively [96]. In Nepal, the average age of infertile women was 27.44±5.214 years attending the infertility clinic of a tertiary hospital [142]. Another Nepalese study reported that the majority (51.52%) of infertility females were aged 26-30 [143].…”
Section: Discussionmentioning
confidence: 99%
“…The women are more exposed during treatment and report stronger reactions both to infertility and treatment overall (20). For this reason, infertile women are more burdened by infertility stress and had stronger emotional reactions to infertility when compared to the men (21).…”
Section: Introductionmentioning
confidence: 99%